A Critical Evaluation of the International Affective Picture System in the Study in the Study of Emotion - Czekóová, Kristína (2011)
The main focus of this thesis is on one of the most extensively used methods for eliciting emotions - International Affective Picture System (IAPS). IAPS is a large set of photographs that depict diverse semantic content including natural sceneries, food, animals, violence, objects of everyday use, accidents, pollution, erotic pictures, and so forth. The theory behind the IAPS method relies on a dimensional view that defines all emotions as a coincidence of values on three major dimensions: valence, arousal, and dominance. Each photograph within the system is defined by normative ratings for all three dimensions. The purpose of developing the IAPS was to facilitate comparisons between and replications of the results from studies on emotion from different laboratories. To this end, normative ratings (mean values of evaluations per picture) on all three dimensions have been acquired and many researchers have been selecting their stimuli from the IAPS database based on these norms.